2023
DOI: 10.3390/s23062988
|View full text |Cite
|
Sign up to set email alerts
|

Acoustoelectric Effect of Rayleigh and Sezawa Waves in ZnO/Fused Silica Produced by an Inhomogeneous In-Depth Electrical Conductivity Profile

Abstract: The acousto-electric (AE) effect associated with the propagation of Rayleigh and Sezawa surface acoustic waves (SAWs) in ZnO/fused silica was theoretically investigated under the hypothesis that the electrical conductivity of the piezoelectric layer has an exponentially decaying profile akin to the photoconductivity effect induced by ultra-violet illumination in wide-band-gap photoconducting ZnO. The calculated waves’ velocity and attenuation shift vs. ZnO conductivity curves have the form of a double-relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to the theoretical predictions of Ref. [18], it was demonstrated that the photoconductive ZnO induces a short-circuiting effect of the electric potential Φ associated with the SAW. As a result of the UV absorption from the bottom side, the electric potential of the Rayleigh wave is expected to be null at the quartz/ZnO interface, and concentrated inside the piezoelectrically active portion of the ZnO layer (not involved in the UV absorption) where it reaches a peak at the ZnO/air interface where the IDTs were located.…”
Section: Saw Uv Sensormentioning
confidence: 96%
See 1 more Smart Citation
“…According to the theoretical predictions of Ref. [18], it was demonstrated that the photoconductive ZnO induces a short-circuiting effect of the electric potential Φ associated with the SAW. As a result of the UV absorption from the bottom side, the electric potential of the Rayleigh wave is expected to be null at the quartz/ZnO interface, and concentrated inside the piezoelectrically active portion of the ZnO layer (not involved in the UV absorption) where it reaches a peak at the ZnO/air interface where the IDTs were located.…”
Section: Saw Uv Sensormentioning
confidence: 96%
“…It is worth mentioning that research in the field of UV SAW sensors started about 20 years ago, and since then it has continued, fueled by ever-new ideas for pursuing the goal of improving the sensors' performance, for example, by exploring different thicknesses of the UV-sensing layer, combining ZnO nanowires or nanosheets with ZnO thin films [5,6], fabricating multilayer structures [7], or exploring harmonic modes [8,9]. The last paragraph compares the performance of the ZnO-based SAW UV sensors described in the available literature (such as working frequency, sensitivity, rise and recovery time, and tested UV power range) and outlines some possible solutions to be explored to improve the sensors' performance.…”
Section: Introductionmentioning
confidence: 99%